2019
DOI: 10.1590/0001-3765201920180248
|View full text |Cite
|
Sign up to set email alerts
|

Jabuticaba (Plinia jaboticaba) skin extracts as inhibitors of phospholipases A2 and proteases

Abstract: The phenolic extracts of jabuticaba skin flour (JSF) were characterized by HPLC, and evaluated for their modulating action upon phospholipases A 2 and proteases of snake venom, aiming at their possible use in the treatment of the various diseases associated with the action of venom toxins. Two types of extracts were prepared from JSF: aqueous and methanolic. These extracts, evaluated at different ratios, (venom: extract, m/m), significantly inhibited the phospholipase activity induced by the venom of Bothrops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
(33 reference statements)
0
4
0
2
Order By: Relevance
“…Thrombolysis induced by B. moojeni and C. d. terrificus venoms was inhibited by both extracts (by 32-83% and 51-83% for the aqueous and methanolic extracts, respectively). [13] Essential oil from Lippia origanoides Inhibition of PLA 2 activity. Potentiation of hemolytic activity in preincubation protocols and presence of prothrombotic activity.…”
Section: Substance(s) Activity Evaluated Main Findings Referencementioning
confidence: 99%
“…Thrombolysis induced by B. moojeni and C. d. terrificus venoms was inhibited by both extracts (by 32-83% and 51-83% for the aqueous and methanolic extracts, respectively). [13] Essential oil from Lippia origanoides Inhibition of PLA 2 activity. Potentiation of hemolytic activity in preincubation protocols and presence of prothrombotic activity.…”
Section: Substance(s) Activity Evaluated Main Findings Referencementioning
confidence: 99%
“…Several investigations involve mechanisms of action of natural compounds that act as enzymatic inhibitors, and the main classes of toxins used as targets are those involved in inflammatory response and hemostasis (phospholipases A2, metalloproteases, and serine proteases) (Bijak et al, 2014;Braga et al, 2019;Marques et al, 2019). However, mechanisms of interaction between enzymes and natural compounds are poorly described and require extensive studies of structural and functional characterization (Mourada-Silva et al, 2016), thus enabling future applications of these compounds in the therapy of human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some studies have demonstrated that plant extracts [21][22][23] and their isolated metabolites [24], including marine sponge extracts [25] might exhibit therapeutic properties to reduce some effects caused by Lachesis venoms. In addition, our group has also demonstrated that N-acetyl-L-cysteine (NAC), an antioxidant drug, contributes to minimize local and systemic disorders induced by L. m. muta venom in rats, e.g., myotoxicity, hepatotoxicity and inflammation, being a potential supporting therapeutic agent to antivenom therapy [26].…”
Section: Introductionmentioning
confidence: 99%